Leadership Education in the Era of Disruption: What Can Business Schools Offer? - Dovey, Ken (Senate Hall Academic Publishing, 2005)
The paper addresses some of the dilemmas that business schools face in their attempts to teach, in conventional educational settings, practices such as leadership that are profoundly informed by experience. In the initial section of the paper, the recognition of relationship as the primary medium of education is advocated and the implications of this for the integration of leadership theory and practice are explored. Thereafter, the paper offers five generic themes for the content of leadership education programs in business schools and discusses various pedagogical processes through which the effectiveness of this thematic material, in addressing the dilemmas of leadership education in a changing world order, can be enhanced.
Keywords: leadership education; organizational leadership; personal leadership; leadership knowledge; leadership development